Racism and God-Talk A Latino/a Perspective - Rodriguez, Ruben Rosario (New York University Press, 2008)
The apostle Paul wrote that "All of you are one in Christ Jesus." Given Paul's vision of God's kingdom defined by the breakdown of all distinctions and relationships of domination-no longer Jew or Greek, slave or free, male or female-how do we make sense of ethnic particularity within the church's theological formulations?Racism and God-Talk explores the biblical and religious dimensions of North American racism while highlighting examples of resistance within the Christian religious tradition. Social historians have seldom analyzed the problematic of race from a primarily theological perspective. This volume undertakes a critical examination of explicitly theological and confessional perspectives for understanding and transforming North American racism.Rosario Rodriguez offers insights from Latino/a theology for broader scholarly and social discussions concerning racism, borders, and immigration. The first to analyze race and racism from a Latino/a theological perspective, the volume makes use of a broadened conceptualization of "mestizaje," or mutual cultural exchange, to challenge the church to recognize the effects of racial and ethnic particularity in all theological construction
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mrz 2022)
Keywords: RELIGION / Christianity / General; Race relations -- Religious aspects -- Christianity; Race relations; Racism -- Religious aspects -- Christianity; Racism -- North America; Theology -- Latin America; Theology -- North America